2018
DOI: 10.1146/annurev-psych-122414-033653
|View full text |Cite
|
Sign up to set email alerts
|

Principles and Challenges of Applying Epigenetic Epidemiology to Psychology

Abstract: The interplay of genetically driven biological processes and environmental factors is a key driver of research questions spanning multiple areas of psychology. A nascent area of research focuses on the utility of epigenetic marks in capturing this intersection of genes and environment, as epigenetic mechanisms are both tightly linked to the genome and environmentally responsive. Advances over the past 10 years have allowed large-scale assessment of one epigenetic mark in particular, DNA methylation, in human p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
88
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(98 citation statements)
references
References 146 publications
3
88
0
3
Order By: Relevance
“…Further, the best method to correct for interindividual variability in cell type is still highly debated (McGregor Labbe, & Greenwood, 2017) which is further complicated by the lack of well-characterized reference profiles for young child saliva. Regardless, future environmental epigenetics studies will benefit from controlling for this important type of variation (Jones et al, in press). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the best method to correct for interindividual variability in cell type is still highly debated (McGregor Labbe, & Greenwood, 2017) which is further complicated by the lack of well-characterized reference profiles for young child saliva. Regardless, future environmental epigenetics studies will benefit from controlling for this important type of variation (Jones et al, in press). …”
Section: Discussionmentioning
confidence: 99%
“…Although there is prior evidence that NR3C1 promoter DNAm is associated with gene expression (Turecki & Meaney, 2016), future longitudinal epigenetics research will benefit from assessing whether the DNAm changes observed alter gene expression (Jones et al, in press). …”
Section: Discussionmentioning
confidence: 99%
“…Below, 3 key areas are discussed that can help clarify the role of DNAm in the link between adversity and mental health. We note that other areas not covered here are also important, such as genetic influence, cellular heterogeneity, temporal variability, replication and functional characterization of DNAm [2, 11]. …”
Section: Discussionmentioning
confidence: 99%
“…In recent years, genome-wide DNAm studies have become more popular, due to their increased affordability and data content [11]. The study of Cecil et al [11] reviewed above may be an exemplar, as the top loci formed a network that was plausibly linked with neurodevelopmental risk for substance use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation